Expression of Candida intermedia GXF1 Improves Xylose Transport in Saccharomyces cerevisiae - Regmi, Priti; Bhattarai, Tribikram (Journal of Nepal Biotechnology Association, 2026)
The heterologous expression of the GXF1 xylose transporter from Candida intermedia was investigated in Saccharomyces cerevisiae DTY165 to evaluate the role of xylose transport in a strain lacking engineered xylose-metabolizing pathways. Introduction of GXF1 led to increased xylose uptake and improved growth when xylose was used as the sole carbon source, as evidenced by a higher specific growth rate and faster depletion of extracellular xylose compared to the empty vector control. Enhanced intracellular accumulation of xylose further supported the contribution of GXF1 to transport efficiency. Despite improved xylose uptake, ethanol production from xylose remained low, and only small increases in ethanol levels were observed in both glucose- and xylose-containing media. These findings indicate that improving xylose transport alone is not sufficient to achieve substantial ethanol production in S. cerevisiae. Instead, effective conversion of xylose to ethanol will likely require additional engineering of downstream xylose-utilization pathways. Overall, this study highlights the importance of coupling enhanced xylose transport with metabolic pathway optimization for meaningful ethanol production.